2018
DOI: 10.1186/s12974-018-1343-x
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef-induced lncRNA AK006025 regulates CXCL9/10/11 cluster gene expression in astrocytes through interaction with CBP/P300

Abstract: BackgroundHIV-associated neurocognitive disorder (HAND) is a neurodegenerative disease associated with persistent neuroinflammation and subsequent neuron damage. Pro-inflammatory factors and neurotoxins from activated astrocytes by HIV-1 itself and its encoded proteins, including the negative factor (Nef), are involved in the pathogenesis of HAND. This study was designed to find potential lncRNAs that regulate astrocyte functions and inflammation process.MethodsWe performed microarray analysis of lncRNAs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 63 publications
(71 reference statements)
0
25
0
Order By: Relevance
“…Further, they suggested that these effects occurred through an lncRNA-protein interaction with the transcription factor CREB (cAMP response element-binding protein) binding protein (CBP/P300) and the nuclear factor kappa-light-chain enhancer of activated B cells (NFκB) p65 isoform. This association/and or interaction of AK006025 with CBP/P300 and NFκB p65, resulted in an enrichment of CBP/P300 and NFκB p65, as well as an increase in acetylation (H3K27ac), a marker for an active promoter, at the promoter sites of CXCL9, CXCL10, and CXCL11 genes [82]. However, the authors did not elucidate the full mechanism of this lncRNA.…”
Section: Lncrnas Involved In Disease Progression or Secondary Diseasementioning
confidence: 98%
See 3 more Smart Citations
“…Further, they suggested that these effects occurred through an lncRNA-protein interaction with the transcription factor CREB (cAMP response element-binding protein) binding protein (CBP/P300) and the nuclear factor kappa-light-chain enhancer of activated B cells (NFκB) p65 isoform. This association/and or interaction of AK006025 with CBP/P300 and NFκB p65, resulted in an enrichment of CBP/P300 and NFκB p65, as well as an increase in acetylation (H3K27ac), a marker for an active promoter, at the promoter sites of CXCL9, CXCL10, and CXCL11 genes [82]. However, the authors did not elucidate the full mechanism of this lncRNA.…”
Section: Lncrnas Involved In Disease Progression or Secondary Diseasementioning
confidence: 98%
“…However, due to the poor conservation of lncRNAs between species, it would be beneficial to determine the effect in human astrocytes. Nevertheless, the paper demonstrates the effects of HIV-1 accessory proteins, such as Nef [82] on the non-coding transcriptome, and how this could contribute towards secondary disease outcomes associated with HIV-1 disease progression.…”
Section: Lncrnas Involved In Disease Progression or Secondary Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Although these RBPs have been known to play important cellular roles by interacting with mRNAs (Gerstberger et al 2014;Dixit and Lukeš 2018;Moore and von Lindern 2018), recent work has demonstrated the importance of RBPs and their interactions with various types of noncoding RNA such as microRNAs, small nucleolar RNAs, long-noncoding RNA, piRNA, and viral RNA (Bagni and Lapeyre 1998;Jiang and Coller 2012;Ciafrè and Galardi 2013;Falaleeva et al 2016;Zealy et al 2017;Grzechnik et al 2018;Lei et al 2018;Tedeschi et al 2018;Baou et al 2011;Zhou et al 2018;Qiao et al 2019;Yang et al 2019). The formation of RNP complexes acts to regulate essential cellular functions from cell division to cell death, transcription to post-translational gene regulation, and downstream functions (Clayton and Shapira 2007;Glisovic et al 2008;Kishore et al 2010;Brinegar and Cooper 2016).…”
Section: Introductionmentioning
confidence: 99%